A chaetetid sponge assemblage from the Desmoinesian (Upper Moscovian) Buckhorn Asphalt Quarry lagerstätte in Oklahoma, USA - Seuß, Barbara; Senowbari-Daryan, Baba; Nützel, Alexander; Dittrich, Sebastian; Neubauer, Jürgen; Neubauer, Jürgen (Rivista Italiana Di Paleontologia E Stratigrafia, 2014)
The first detailed study on chaetetids from the Buckhorn Asphalt Quarry Lagerstätte is presented. Among the investigated specimens we found two samples (chaetetid specimens 2 and 6) that are different from all others in the quarry. Thin sections of these display a complex fragmentation of these Buckhorn chaetetids. Additionally, one of these samples contains two chaetetid morphotypes growing side by side, thus, in the same paleoenvironment. These specimens differ in their mode of growth (laminar and domical), which suggests that chaetetid growth was most likely influenced by genetic factors rather than by the paleoenvironment. We observed a feature, not hitherto reported as far as we are aware, on the surface of chaetetids; namely a regular clustering of seven tubules surrounding a central tubule. This feature could have had an exhalant function. Mineralogical analyses of the skeleton indicate primary high magnesian-calcite mineralogy, which is in accordance with reports in the literature. Cements precipitated during diagenesis are either calcite or dolomite and, where associated with microbial mats, they may contain a distinct amount of manganese. The comparison of the chaetetid skeletons from the Buckhorn Asphalt Quarry leads to the impression, that they represent various morphotypes or even species. Because of the lack of unique features, we have refrained however, from describing new species.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LP.achaet
Keywords: Buckhorn asphalt quarry; Chaetetida; Hypercalcified sponges; Pennsylvanian; Taphonomy

Does Ordinary Portland Cement contain amorphous phase? A quantitative study using an external standard method - Jansen, Daniel; Stabler, Christopher; Götz-Neunhoeffer, Friedlinde; Dittrich, Sebastian; Neubauer, Jürgen (Powder Diffraction, 2011)
A suitable external standard method which was first described by O'Connor and Raven (1988) ("Application of the Rietveld refinement procedure in assaying powdered mixtures," Powder Diffr.3, 2-6) was used to determine the quantitative phase composition of a commonly used Ordinary Portland Cement (OPC). The method was also applied in order to determine amorphous contents in OPC. Also investigated were the impact of atomic displacement parameters and the microstrain on the calculated amorphous content. The investigations yielded evidence that said parameters do indeed exert an influence on the calculated amorphous content. On the basis of the data produced we can conclude that the method used is entirely to be recommended for the examination of OPC. No significant amorphous content could be proven in the OPC used. © 2011 International Centre for Diffraction Data.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.LM.doesor
Keywords: Amorphous content; External standard; G factor; Ordinary Portland Cement

Hydration of Portland cement with high replacement by siliceous fly ash - Deschner, Florian; Winnefeld, Frank; Lothenbach, Barbara; Seufert, Sebastian; Schwesig, Peter; Dittrich, Sebastian; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen (Cement and Concrete Research, 2012)
The effects of two different low calcium fly ashes on the hydration of ordinary Portland cement (OPC) pastes containing 50 wt.% of fly ash were investigated over a hydration time of 550 days. The results were compared with a reference blend of OPC containing 50 wt.% of inert quartz powder allowing the distinction between "filler effect" and pozzolanic reaction. Until 2 days, no evidence of fly ash reaction was measured and its influence on the hydration is mainly related to the filler effect. From 7 days on, the effects of the pozzolanic reaction were observed by the consumption of portlandite, the change of the pore solution chemistry, the formation of a presumably water-rich inner hydration product and the change of the C-S-H composition towards higher Al/Si ratio compared to the C-S-H of neat OPC. Additional strength due to the pozzolanic reaction developed after 28 days of hydration. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LM.hydrat
Keywords: Blended Cement (D); Filler (D); Fly ash (D); Hydration (A); Pozzolan (D)

Synthesis of Eu-doped SrAl2O4 nanophosphors by CO2 laser vaporization - Zollfrank, Cordt; Gruber, Sabine; Batentschuk, Miroslaw; Osvet, Andres; Götz-Neunhoeffer, Friedlinde; Dittrich, Sebastian; Grabow, Janet; Kurland, Heinz-Dieter; Müller, Frank A. (Acta Materialia, 2013)
A new method of synthesizing spherical nanoparticles with photoluminescent spinel structures using a CO2 laser co-vaporization technique (CoLAVA) is presented. The method applies homogeneous mixtures of oxidic precursors such as Al2O3, SrO and Eu2O 3 and allows the fabrication of quantities exceeding 10 g h -1. During the CoLAVA process, the educt oxides are reacted by a gas phase condensation yielding amorphous spherical particles with diameters ranging from 10 to 100 nm. The as-prepared materials exhibit red emission at 625 nm (1.98 eV) due to the incorporated Eu3+. Temperature treatment up to 1200 C under a reducing atmosphere yielded crystalline particles of the same size, which were slightly sintered. These particles consisted of >90 wt.% SrAl2O4 with minor fractions of Sr3Al 2O6 and SrCO3. The amount of the SrAl 2O4 spinel increased with increasing temperature, whereas the accompanying phases were decreased. A strong green emission centered at 525 nm (2.36 eV) detected at RT was observed at an onset temperature of 900 C, which is due to the presence of Eu2+ in the crystal lattice of SrAl 2O4. The red emission was not observed at higher annealing temperatures. The CoLAVA method represents a fast and facile route for the fabrication of nano- to microstructured phosphor materials for a variety of engineering applications. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.LM.synthe
Keywords: Laser vaporization; Nanoparticles; Photoluminescence

The influence of fly ash on the hydration of OPC within the first 44 h - A quantitative in situ XRD and heat flow calorimetry study - Dittrich, Sebastian; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2014)
We used in-situ XRD and heat flow calorimetry to investigate the first 44 h of hydration of Ordinary Portland Cement (OPC) blended with siliceous fly ash (FA). By recalculating the heat flow using XRD data it was possible to establish the direct influence of FA on the silicate and aluminate reaction of the OPC hydration in combination with absolute phase quantities. A retarding effect of FA on the silicate reaction was detected, probably induced by the adsorption of Ca2 + ions on the FA surface. The aluminate reaction proved to be influenced by FA. Thereby the filler effect produces an acceleration of the reaction by providing additional nucleation sites. Additionally the reaction itself is very sensitive to the chemical composition of FA. Readily available SO3 seems to be the factor responsible for retarding the aluminate reaction. The increasing of the effective w/s-ratio seems to have only a slight influence on the hydration behavior. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.LM.theinf
Keywords: Calorimetry (A); Early hydration; Fly ash (D); Portland cement (D); X-ray diffraction (B)